2003
DOI: 10.1046/j.1440-1797.2003.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibody‐negative pauci‐immune crescentic glomerulonephritis associated with rheumatoid arthritis: An unusual case report

Abstract: Clinically relevant renal lesions in rheumatoid arthritis (RA) are not common. More often renal involvement is related to complications of therapy than the disease itself. The most common forms of primary renal disease in RA are membranous glomerulonephropathy and a pure mesangial proliferative glomerulonephritis. Some studies have described the association between crescentic glomerulonephritis (crescentic GN) and RA, but they were all found to be perinuclear antineutrophil cytoplasmic antibody (p-ANCA) positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…However, our patient presented within 1 year of receiving her seropositive rheumatoid arthritis diagnosis and did not have erosive arthritis. To the best of our knowledge, only one case of rheumatoid arthritis-associated ANCA-negative crescentic glomerular nephritis has been reported to date [10]. Crescentic glomerular nephritis needs aggressive treatment with immunomodulators, including intravenous methylprednisolone pulses and cyclophosphamide [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our patient presented within 1 year of receiving her seropositive rheumatoid arthritis diagnosis and did not have erosive arthritis. To the best of our knowledge, only one case of rheumatoid arthritis-associated ANCA-negative crescentic glomerular nephritis has been reported to date [10]. Crescentic glomerular nephritis needs aggressive treatment with immunomodulators, including intravenous methylprednisolone pulses and cyclophosphamide [14].…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement in rheumatoid arthritis includes secondary amyloidosis, nephrotoxicity of the drugs used for treatment, and rheumatoid nephropathy as extra-articular manifestations [15]. In rheumatoid nephropathies, mesangial glomerular nephritis is the most frequent histological lesion, followed by minimal change glomerulopathy, membranous glomerulopathy, and crescentic glomerular nephritis [1, 2, 610]. Crescentic glomerular nephritis is rare, and more than 50% of the patients have features of systemic vasculitis, with almost all having perinuclear antineutrophil cytoplasmic antibody positivity [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have followed ANCA-negative patients after treatment have found that renal outcomes were either comparable or worse amongst ANCA-negative patients, with the overall survival remaining equal between the two groups [4, 5, 6, 7]. There are cases of pauci-immune crescentic GN that co-exist with other autoimmune conditions, including RA, but with uncertain renal significance and variable outcomes [8, 9, 10, 11, 12]. An important additional cause of crescentic GN can be infection [13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%